A NEEDS ANALYSIS OF TECHNOLOGY-INTEGRATED BASIC ENGLISH GRAMMAR COURSE IN THE INDONESIAN CONTEXT - Suharti, Dwi Sloria; Musthafa, Bachrudin; Yusuf, Fazri Nur (International Journal of Education, 2022)
Needs analysis is essential for developing a curriculum and teaching materials. Integration of technology in courses provides a supportive environment for learners across a wide range of courses. However, the needs analysis on the technology-integrated Basic English Grammar course learning is insufficient. This report aims to determine students' needs for studying Basic English Grammar courses through technology integration. For this purpose, the researchers used a descriptive qualitative design by distributing questionnaires. Twenty-four students completed the questionnaire, and the researchers recruited several students for interviews. The results of this study reveal students' expectations for technology-integrated assignments, such as submitting writing caption chores to Instagram, with a 48 per cent success rate. The technology-integrated Basic English Grammar course learning presences depict the most commonly used technologies such as YouTube, Instagram, the Quiz app, Google Classroom, Webbing, and e-Books. The researchers identified the lack of internet connection and an overabundance of information that perplexes students—this suggests the necessity to provide training to cope with the technological challenges of learning Basic English Grammar. The study proposes a teaching-learning situation in the Basic English Grammar course with technology integration as learning activities materials in the syllabus so that the teachers as the curriculum makers can develop the curriculum according to the needs of students. This report highlights that lecturers and universities perform periodic assessments of their students' needs as a basis for developing a curriculum with these reflective needs. In addition, the pedagogical implications for technology-integrated tools in the Basic English Grammar course are discussed.